PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. MARGI WAHYU CABANG PALEMBANG - Noviarni Noviarni; Martha Rianthy (JURNAL KOMPETITIF, 2022)
The purpose of this study was to determine the effect of providing incentives, work motivation of providing incentives and work motivation together on the performance of employees of PT. Margi Wahyu Palembang Branch. This study uses a survey method with a saturated sample of 53 employees as respondents. The data taken are primary data and secondary data.The results of the study show that there is an effect of providing incentives on employee performance, this is indicated by the value of sig t <0.05. If employees always get piecework, always get production bonuses, always get commissions, and have people skills, then employee performance will be better. There is an influence of work motivation on employee performance, this is indicated by the value of sig t <0.05. Employee Performance PT. Margi Wahyu Palembang Branch is influenced by the work motivation of the employees themselves, meaning that the better the fulfillment of physiological, security, sociological, esteem, and self-actualization needs of employees, the higher their performance. There is a joint effect of providing incentives and work motivation on employee performance, this is indicated by the value of sig F < 0.05. Employee performance is influenced jointly by the provision of incentives and work motivation. This means that if there is an increase in the provision of incentives and work motivation, it will increase employee performance.Keywords ;  Incentives; Work Motivation; Performance